SUPPLEMENTAL STUDY ON ICHTHYOFAUNA OF CORAL REEF FISHES IN NHA TRANG BAY MARINE PROTECTED AREA, KHANH HOA PROVICE - Quan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2009)
Based on the original _ materials collected at the field surveys carried out in the years of 2002-2006 at Nha Trang Bay marine protected area (MPA), Khanh Hoa province, there were 420 species, 198 genera and 77 families have been recorded in the coral reef fish fauna . 23 species were recognized as new records for Vietnam Marine Fish Checklist and 128 species were added in the list of coral reef fishes in Nha Trang Bay that contributed by previous authors. Most of the coral reef fishes occur in the vicinity of the MP A ar,e rated as small size (TL< I Scm, occupying 80% of the total individual count numbers: families Pomacentridae, Chaetodontidae, Apogonidae and Labridae. There are 18 common species found in all the s u rvey transects by the frequency catch of 80- I 00%. The individual density of the cor a l reef fish communities in the core zone was rather higher than that of the buffer zone: 831 individual/500m: and I 21 individual/500m 2 , respectively . At the same survey sites, the individual density is higher at the reef flat to compare with that of the reef slope with estmated value of 40%. However, commerical high value families such as Scaridae, Lutjanidae, Caesionidae, Lethrinidae, Serranidae distribute mainly at the reef slope . For maintenace of the sustainable natural resources, it is suggested that instututional conservation strategy should be prioritized, reduction of- the commercial fishing practices, and diverification of the ecological tourism activities. . . Thus these tasks will help to improve the livelihoods of the local communities living around the MPA.